Citrus flavonoid extracts alter the profiling of rumen antibiotic resistance genes and virulence factors of dairy cows - Yu, Shiqiang; Li, Liuxue; Zhao, Huiying; Liu, Ming; Jiang, Linshu; Zhao, Yuchao (Frontiers in Microbiology, 2023)
Citrus flavonoid extracts (CFE) have the potential to reduce rumen inflammation, improve ruminal function, and enhance production performance in ruminants. Our previous studies have investigated the effects of CFE on the structure and function of rumen microbiota in dairy cows. However, it remains unclear whether CFE affects the prevalence of antibiotic resistance genes (ARG) and virulence factors genes (VFG) in the rumen. Therefore, metagenomics was used to identify the rumen ARG and VFG in lactating dairy cows fed with CFE diets. The results showed that CFE significantly reduced the levels of Multidrug and Antiphagocytosis in the rumen (P < 0.05) and increased the levels of Tetracycline, Iron uptake system, and Magnesium uptake system (P < 0.05). Furthermore, the changes were found to have associations with the phylum Lentisphaerae. It was concluded that CFE could be utilized as a natural plant product to regulate virulence factors and antibiotic resistance of rumen microbiota, thereby improving rumen homeostasis and the health of dairy cows.